Rahasia Sukses di Masa Pensiun: Menyingkap Hubungan Kesejahteraan Subjektif dan Psikologis dengan Flourishing - Akhmad, Satria Kamal; Hamidah; Surjaningrum, Endang R. (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Psychological issues are often overlooked in retirement, unlike physical and financial aspects that are deemed to be more conspicuous and comprehensible. Whereas, happiness is our primary goal and reflects mental health. The concept of flourishing is frequently used to depict high levels of mental well-being. Despite debates surrounding hedonic and eudaemonia perspectives, this study examines whether subjective and psychological well-being can predict flourishing in retirees. The study involves 72 members of the University of Brawijaya Retirees Association who have retired for 3-12 years. Data were collected using the PERMA-Profiler, SWLS, SPANE, and PWBS. The results indicate that flourishing in retirees is influenced by subjective and psychological well-being simultaneously (R=0.465, R2=0.216, p=0.000), contributing to 19.3%. Partially, flourishing is more influenced by psychological well-being but not by subjective well-being. Therefore, psychological well-being is the primary predictor of flourishing among members of the University of Brawijaya Retirees Association.